Recent Advances in the Development of Vaccines for Diabetes, Hypertension, and Atherosclerosis - Kongye Lu; Benli Su; Xiuxiang Meng (Journal of Diabetes Research)
Vaccines are commonly used in the prevention of infectious diseases. The basic principle of vaccination is to use specific antigens, endogenous or exogenous to stimulate immunity against the specific antigens or cells producing them. Autoantigen or oligo vaccination has been used for disease animal models. More recently humanized monoclonal antibodies have been successfully used for the treatment of neoplastic disorders or familial hypercholesterolemia. Humanized monoclonal antibody therapy needs repeated injection, and the therapy is expensive. Therapeutic vaccination can lead to persistent immunized or immune tolerant against the therapeutic molecule(s) or site. However, immunization against those endogenous substances may also elicit persistent autoimmune reaction or destruction that do harm to health. Therefore, rigorous studies are needed before any clinical application. In this review, we briefly reviewed vaccines used in protection against common metabolic diseases including atherosclerosis, hypertension, and diabetes mellitus.